Exploring single-domain antibody thermostability by molecular dynamics simulation. Issue 14 (22nd September 2019) - Mohseni, Ammar; Molakarimi, Maryam; Taghdir, Majid; Sajedi, Reza H.; Hasannia, Sadegh
Abstract: Single-domain antibodies also known as nanobodies are recombinant antigen-binding domains that correspond to the heavy-chain variable region of camelid antibodies. Previous experimental studies showed that the nanobodies have stable and active structures at high temperatures. In this study, the thermal stability and dynamics of nanobodies have been studied by employing molecular dynamics simulation at different temperatures. Variations in root mean square deviation, native contacts, and solvent-accessible surface area of the nanobodies during the simulation were calculated to analyze the effect of different temperatures on the overall conformation of the nanobody. Then, the thermostability mechanism of this protein was studied through calculation of dynamic cross-correlation matrix, principal component analyses, native contact analyses, and root mean square fluctuation. Our results manifest that the side chain conformation of some residues in the complementarity-determining region 3 (CDR3) and also the interaction between α-helix region of CDR3 and framework2 play a critical role to stabilize the protein at a high temperature. Communicated by Ramaswamy H. Sarma